Verification of Changes in Body Proportions in Humans - Fujii, Katsunori (European Journal of Applied Sciences, 2021)
So far, the growth curves proposed by Scammon (1930) have been often used to advantage when explaining the changes in human proportions. With regard to these explanations, the growth was understandable if seen as the relative growth of the general growth pattern for things such as height and weight and the neural growth pattern showing growth of the head. However, the point here is that the validity the logic for the growth curves proposed by Scammon almost 90 years ago should obviously be tested. Even assuming that the growth curves of Scammon (1930) were to be re-examined, the changes in human proportions can probably not be verified simply with the differences between the general and neural type growth patterns alone. Thus, it is necessary to verify the actual height and weight growth patterns and the head growth pattern. Therefore, the present study attempts to verify the changes in human proportion by applying the wavelet interpolation model to growth distance values obtained through measurements of growth in height and head circumference from early childhood to adults, and to analyze the behavior of the velocity curves of height and head circumference derived as differential curves. As result, this study was able to provide unequivocal findings on the changes in proportion by applying the wavelet interpolation model proposed by the author (1999) (2006). However, the study had the limitations that there was no longitudinal data on the organs, actual face length, or longitudinal data on head circumference.